1986
DOI: 10.1073/pnas.83.6.1906
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to human respiratory syncytial virus (RSV) infection induced by immunization of cotton rats with a recombinant vaccinia virus expressing the RSV G glycoprotein.

Abstract: A cDNA copy of the G glycoprotein gene of human respiratory syncytial virus (RSV) was placed under control of a vaccinia virus promoter and inserted into the thymidine kinase locus of the vaccinia virus genome. The recombinant vaccinia virus retained infectivity and expressed a 93-kDa protein that migrated with the authentic RSV G glycoprotein upon polyacrylamide gel electrophoresis. Glycosylation of the expressed protein and transport to the cell surface were demonstrated in the absence of other RSV proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 47 publications
2
55
1
Order By: Relevance
“…The corresponding three recombinant vaccinia viruses containing truncated RSVG genes but without NANP sequences were constructed as controls and called VG2, VG3, and VG4. RSVG is heavily glycosylated, and roughly 60% of the apparent molecular weight of this protein is believed to be contributed by the carbohydrate moieties (11,28). To detect and characterize the hybrid proteins expressed by the recombinant viruses, extracts of CV-1 cells infected with each of the three recombinant viruses, as well as control wild-type virus-infected and uninfected cells, were electrophoresed in 10% polyacrylamide gels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding three recombinant vaccinia viruses containing truncated RSVG genes but without NANP sequences were constructed as controls and called VG2, VG3, and VG4. RSVG is heavily glycosylated, and roughly 60% of the apparent molecular weight of this protein is believed to be contributed by the carbohydrate moieties (11,28). To detect and characterize the hybrid proteins expressed by the recombinant viruses, extracts of CV-1 cells infected with each of the three recombinant viruses, as well as control wild-type virus-infected and uninfected cells, were electrophoresed in 10% polyacrylamide gels.…”
Section: Methodsmentioning
confidence: 99%
“…The complete gene for RSVG, present as a BamHI fragment in M13mp18 (11), was mutagenized at proline residues 71, 180, and 230 by using the oligonucleotides d(AAGTCACACCCGGGTAAGGATCCA CAACTGCAA), d(GCAACAATCCCGGGTAAGGATCCA CCTGCTGGGC), and d(CCACCAAGCCCGGGTAAGG AT), respectively. Mutagenesis introduced a SmaI site, followed by a termination codon in frame with the RSVGcoding sequence and a BamHI site, after each of the prolines mentioned previously.…”
Section: Methodsmentioning
confidence: 99%
“…The protective immunity induced by VV recombinants encoding the RSV F and G proteins has been described both in mice Stott et al, 1986) and cotton rats (Olmsted et al, 1986;Elango et al, 1986). The studies in mice showed that infection with 107 p.f.u, ofF or G VV intraperitoneally protected mice from intranasal infection with natural RSV 3 weeks after priming.…”
Section: Induction Of Th Cell Memory Specific[or Different Rsv Proteinsmentioning
confidence: 96%
“…Additionally, other eukaryotic viral glycoproteins have been correctly glycosylated and transported within recombinant vaccinia virus-infected cells (for review, see Mackett & Smith, 1986). The infectivity of recombinant vaccinia viruses has enabled animals to be vaccinated and protected against subsequent challenge with influenza virus (Smith et al, 1983b), herpes simplex virus (Paoletti et al, 1984;Cremer et al, 1985), hepatitis B virus , rabies virus Wiktor et al, 1984), vesicular stomatitis virus and human respiratory syncytial virus (Ball et al, 1986;Elango et al, 1986). This protection may be attributable to the ability of the recombinant viruses to induce both antibody and cytotoxic T cell responses specific for the foreign gene product (Bennink et al, 1984Wiktor et al, 1984;Yewdell et al, 1985).…”
Section: -7619 © 1987 Sgm Fm Tomley and Othersmentioning
confidence: 99%